KETEBALAN MEDIA TANAM DAN DOSIS DOLOMIT TERHADAP HASIL JAMUR MERANG (Volvariella volvaceae) - Sudana, Ari; Maryani, Yekti; Darini, Maria Theresia (JURNAL ILMIAH AGROUST, 2018)
The study aims to determine the effect ofthickness of mushroom media and dolomite dosage on growth and yield of straw mushroom. The experiment was carried out in mushroom houseowned by mushroom farmers at Wates street Sedayu, Bantul District, Spesial Region of Yogyakarta. The agro-climatological properties of the study location were temperature 24.5 oC, at an altitude of ± 149 m above sea level, with annual rainfall of 1500-2000 mm per year, air humidity of 65-95%, it was conducted  in January untill February 2018.The study was arranged in a factorial Completly Randomized Design (CRD) with 3 replications. The first factor was media thickness namely 10,15 and 20 cm. The second factor was dosage of dolomite fertilizer namely  1, 2 and 3%. so that 9 treatments unit were obtained, and each treatment was replications three time.Observation of variables included fresh weight per fruit body, fresh weight of fruit body per plot, fresh weight of total fruit body harvest per plot, height of fruit body, fruit body diameter and frequent harvest.The data analysis by analysis of varian followed Duncan’s Multiple Range Test at 5% significance level. The result of analysis shows that there wasn’t interaction between media thickness and dolomite dose in all observation variables. The highest total body weight was obtained at a thickness medium 20 cm, while dolomite at a dosage 1%